A. Pepper resistance to pepymv and pepymv-lins and development of resistant hybrids. - Braga, Renato; Pavan, Marcelo Agenor [UNESP] (FapUNIFESP (SciELO), 2021)
Pepper yellow mosaic virus (PepYMV) is the most important Potyvirus infecting plants of Capsicum genus in Brazil. Losses can reach 100% if the infection occurs at the beginning of cultivation. Genetic resistance is the major method to control this disease. In 2009, a new isolate called PepYMV-Lins was detected breaking the genetic resistance of commercial varieties. This study aimed to search for sources of resistance to this new isolate, investigate the inheritance of resistance, incorporate in elite inbred lines and develop new hybrids of resistant peppers showing good agronomic performance. Among the accessions of the germplasm bank of Sakata Company, there were six hot peppers and two sweet peppers that carried combined resistance to PepYMV and PepYMV-Lins isolates. The latter two were chosen to continue the study of resistance introduction. The inheritance study indicated that the genetic resistance of the two sweet pepper accessions is monogenic and recessive. They were crossed with the Company’s elite pepper inbred lines with the aim of developing commercial hybrids of the conic type. To accelerate the breeding study, the technique of development and stabilization of lines via double-haploid was used. The new inbred lines obtained through this methodology were crossed to generate hybrids. The newly developed hybrids were resistant to PepYMV and PepYMV-Lins isolates. Two of them (AF23571 and AF23579) were identified to have high agronomic stability and resistance. Large-scale tests indicated that AF23579 had the best performance. This hybrid is commercially available in the Brazilian market of sweet pepper seeds, where it is named ‘Nocaute’.
Resistência de pimentão ao pepymv e pepymv-lins e obtenção de híbridos resistentes
Keywords: Pepper yellow mosaic virus; Viral disease; ‘Nocaute’